Radiographic kidney measurements in North American pet ferrets (Mustela furo). (8th September 2012) - Eshar, D.; Briscoe, J. A.; Mai, W.
Abstract Objectives The purpose of the current study was to determine normal radiographic kidney ‐measurements in pet ferrets. Methods Kidney length and width dimensions and the length of the second lumbar vertebra (L2) were determined from survey ventrodorsal radiographs in 53 neutered ferrets of various ages, weight and sex, with no evidence of urogenital disease. Kidney dimensions were expressed as a ratio to the body length of L2. Results All ferrets in this study had six lumbar vertebrae. The median length of L2 was 13·3 mm, and was longer in males than females (P=0·0001). The 95% confidence interval for kidney‐length‐to‐L2 ratios was 2·21 to 2·31 for the right and 2·15 to 2·25 for the left. For the kidney‐width‐to‐L2 ratios these intervals were 1·09 to 1·14 for the right and 1·07 to 1·12 for the left kidney. There was a significant association between kidney size and weight or sex but not with age. Clinical Significance The results of this radiographic study may allow practitioners to have a more ‐objective clinical radiographic evaluation of kidney size of pet ferrets based on individual traits.